If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (99 + x) = (176 + y) Remove parenthesis around (99 + x) 99 + x = (176 + y) Remove parenthesis around (176 + y) 99 + x = 176 + y Solving 99 + x = 176 + y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-99' to each side of the equation. 99 + -99 + x = 176 + -99 + y Combine like terms: 99 + -99 = 0 0 + x = 176 + -99 + y x = 176 + -99 + y Combine like terms: 176 + -99 = 77 x = 77 + y Simplifying x = 77 + y
| -9(x+3)+3x+6=5x+9 | | 6.75t+7=15.5t+14 | | 4568b-4=7 | | -v+2=3 | | 116=-4(-4y)-9(2y)+y | | (w*3-9)+(w+4)=(w*3-9)+(w+4) | | 2x+3y=5.13 | | 16+b^2+6b=0 | | 4y^6(y^2+9y+2)= | | 8n^2-3n-16=24 | | -10+3x=-4 | | X+y=y+x+200 | | 57=3v+3 | | 89-116=-4(-4y)-9(2y) | | 4x+6+6x=36 | | x+y+z=2000zxy | | (7x-4x)=y | | -5x-2=-2x-17 | | 0.5(2n-10)=22 | | -4x+5+6x=37 | | 183=3+10x | | 20+x*-4=44 | | 12x-10=8x | | 15n=6+25 | | 15n=6+255 | | 7p-2r-6r-2p= | | 5-7m=5 | | 2(3y+6)=2y+4 | | 6=4(3x+12)+13x | | 17-(2m+7)=5+4m-13 | | 4y^8+36y^7+8y^6= | | 5n+19=20 |